Hydration properties and water structure in aqueous solutions of native and modified cyclodextrins by UV Raman and Brillouin scattering. (25th March 2018) - Bottari, C.; Comez, L.; Paolantoni, M.; Corezzi, S.; D'Amico, F.; Gessini, A.; Masciovecchio, C.; Rossi, B.
Abstract: We have studied aqueous solutions of native and chemically modified cyclodextrins (CDs) by means of UV Raman and Brillouin scattering. Analysis of the spectral profile of the OH‐stretching Raman signal, which is sensitive to the intermolecular organization of water, reveals a remarkable reduction of the population of ordered tetrahedral water structures inside the hydration shell of substituted CDs. As a remarkable result, this destructuring effect seems to be mainly related to the number of substituted hydroxyl groups in the CD ring rather than to the chemical nature of the substituent group. UV Brillouin scattering experiments confirm the structural picture emerging from the UV Raman study, also providing an estimate of the activation energy associated to the collective H‐bond restructuring mechanism in CD solutions. Overall, the results provide a coherent description of the water–solute interactions in aqueous solutions of CDs. Abstract : The intermolecular organization of water around native and chemically modified cyclodextrins have been studied by UV Raman and Brillouin experiments. The progressive disruption of the tetrahedral order of water, found for the substituted forms of cyclodextrins, seems to be mainly related to the average number of substituted OH groups rather than to the chemical nature of the substituent.